2021
DOI: 10.1029/2021jd034797
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 Induced Fingerprints of a New Normal Urban Air Quality in the United States

Abstract: As the 2019 novel Corona virus (COVID-19) spread from China to other parts of the world, various countries imposed lockdown measures one by one. Reports of improved air quality from ground and satellite observations of aerosol optical depth (AOD) and nitrogen dioxide (NO 2 ) soon followed in the media as documented by Kondragunta et al. (2020). The precipitous drops seen in the tropospheric vertical column NO 2, (trop-NO 2 here onward) measured by the Sentinel 5P TROPOspheric Monitoring Instrument (TROPOMI) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Satellite observations show a drastic decline in tropospheric NO 2 vertical column density over China following the outbreak of COVID-19, reflecting reduced fossil fuel usage due to decreases in economic activity and restrictions on travel ( Huang and Sun, 2020 ; Liu et al, 2020 ). Similar declines have also been seen over Italy ( Bauwens et al, 2020 ), India ( ESA, 2020 ), North America ( Goldberg et al, 2020 ; Kondragunta et al, 2021 ; Tzortziou et al, 2021 ) as observed by the TROPOspheric Monitoring Instrument (TROPOMI) and the Ozone Monitoring Instrument (OMI). These satellite-based studies illustrate the importance of spaceborne observations for providing timely and continuous air quality monitoring.…”
Section: Introductionsupporting
confidence: 62%
“…Satellite observations show a drastic decline in tropospheric NO 2 vertical column density over China following the outbreak of COVID-19, reflecting reduced fossil fuel usage due to decreases in economic activity and restrictions on travel ( Huang and Sun, 2020 ; Liu et al, 2020 ). Similar declines have also been seen over Italy ( Bauwens et al, 2020 ), India ( ESA, 2020 ), North America ( Goldberg et al, 2020 ; Kondragunta et al, 2021 ; Tzortziou et al, 2021 ) as observed by the TROPOspheric Monitoring Instrument (TROPOMI) and the Ozone Monitoring Instrument (OMI). These satellite-based studies illustrate the importance of spaceborne observations for providing timely and continuous air quality monitoring.…”
Section: Introductionsupporting
confidence: 62%
“…Precursor emissions and ozone levels in 2020 were anomalous and it is too early to know if emissions will return to their pre‐pandemic levels (Kondragunta et al., 2021 ). Therefore we do not know if the positive ozone trends in the free troposphere above Europe and western North America since 1994 have stopped or if they will resume in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting COVID‐19 pandemic triggered a worldwide economic downturn in 2020 which reduced emissions of ozone precursor gases. These emissions reductions appeared to be related to a range of impacts on observed levels of ozone and particulate matter at the surface and in the free troposphere (Bauwens et al., 2020 ; Clark et al., 2021 ; Cooper et al., 2021 ; Cristofanelli et al., 2021 ; Gkatzelis et al., 2021 ; Keller et al., 2021 ; Kondragunta et al., 2021 ; Le et al., 2020 ; Liu et al., 2020 ; Shi & Brasseur, 2020 ; Sokhi et al., 2021 ; Steinbrecht et al., 2021 ). In general, surface observations from monitoring networks in many nations showed that urban areas with NOx‐limited regimes (e.g., Rio de Janeiro and South African urban areas) experienced ozone decreases, while urban areas with VOC‐limited regimes experienced ozone increases (e.g., urban areas in South Korea and Colombia; Sokhi et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent with the lockdowns, air quality was reported to have improved in many parts of the United States, although air quality changes differed by location. U.S.-based studies have identified certain sourcesin particular, mobile sources and wildfiresthat contributed to air pollution variability during the lockdown period and post-lockdown period in 2020. , However, based on the existing literature on air quality responses to the COVID-19 lockdown (Table S1), it is unclear the extent to which EGU emissions were impacted by mobility and economic changes associated with COVID-19 public health interventions. Since stationary EGUs remain a major contributor to air pollution and greenhouse gas emissions in the United States and previous work has linked mobile emissions changes due to mobility patterns, policymakers will benefit from an understanding of how EGU emissions changed with and after pandemic-initiated shifts.…”
Section: Introductionmentioning
confidence: 99%